2022
DOI: 10.2147/ccid.s350000
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress in Vitiligo Patients: A Neglected but Real-Existing Psychological Impairment

et al.

Abstract: Background Vitiligo is the most common depigmentation disorder. This disease causes disfiguration and induces psychological burdens, leading to significantly impaired quality of life. Limited research about disease-related post-traumatic stress (PTS) has been conducted in vitiligo patients. Objective To evaluate the prevalence, severity, and risk factors of post-traumatic stress in vitiligo patients. Methods This case-control study was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
2
0
3
Order By: Relevance
“…According to Lui's studies, vitiligo was found in 70-80% of subject in the group of 16-30 years and this high percentage was in agreement with our results. 26 Today, it is quite clear that the condition of the skin has a particular impact on the quality of life, considering that it is the most exposed part of the human body, especially when communicating with the environment. The appearance of depigmented macules on the head, neck, face and hands are instantly registered when meeting a person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lui's studies, vitiligo was found in 70-80% of subject in the group of 16-30 years and this high percentage was in agreement with our results. 26 Today, it is quite clear that the condition of the skin has a particular impact on the quality of life, considering that it is the most exposed part of the human body, especially when communicating with the environment. The appearance of depigmented macules on the head, neck, face and hands are instantly registered when meeting a person.…”
Section: Discussionmentioning
confidence: 99%
“…Each item is scored on a scale from four points (3=a lot, 2=moderately, 1=a little, 0=not at all). The total score of DLQI was calculated by summing the score of each of the 10 questions assessed and interpreted: as no impairment of quality of life (0-1), minor damage (2-5), moderate damage (6-10), severe damage (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), or a serious severe impairment (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). In the second questionnaire, the data was filled out by the researcher of the Department of dermatology in the "Remedika" Private General Hospital after a clinical examination of the patient and includes data on age, sex, place of residence, education, marital status, Fitzpatrick skin type, comorbid diseases (hyperlipidemia, diabetes mellitus type 1, hyperthyroidism, hypothyroidism, pernicious anemia, alopecia areata, ophthalmic abnormalities), familial history of the disease, use of alcohol, cigarettes, BMI.…”
Section: Methodsmentioning
confidence: 99%
“…Para exemplificar a relação entre vitiligo e a depressão, Ballone (2007), relata o caso de uma paciente no consultório de psiquiatria, que sem nenhum mistério teve a evolução satisfatória do vitiligo depois do tratamento de depressão. Liu, et al (2022), traz que, o estresse pós-traumático, como a perda de um ente querido, doença grave, problemas financeiros ou problemas de trabalho, podem ser fatores que influenciam o desenvolvimento do vitiligo ou somatiza o avanço da doença. Esses eventos consideráveis na vida de um indivíduo levam a consequências significativas, como ansiedade e depressão, que reduzem sua qualidade de vida e somatizam a doença.…”
Section: Discussionunclassified
“…(Dai et al, 2021). En efecto, Liu et al (2022) investigaron el trastorno de estrés postraumático en 337 pacientes con vitiligo y hallaron que un tercio de los pacientes con vitiligo tenían Estrés postraumático y se confirmó que la décima parte desarrolló Trastorno de estrés Postraumático. Por su parte, Savaş et al (2021) buscaron hallazgos psiquiátricos en grupos de niños y adolescentes con alopecia areata y vitiligo e identificaron que los eventos estresantes fueron más comunes en pacientes pediátricos con vitiligo que en aquellos con alopecia.…”
Section: Estrés Psicológico Y Vitiligounclassified
“…Los hallazgos encontrados afirman que la enfermedad de vitiligo guarda una íntima relación con el estrés psicológico y puede estar relacionado con un desbalance químico en el paciente que posee la enfermedad. De los 23 artículos revisados, la mayoría están a favor de que las personas con vitiligo manejan niveles más altos de estrés, ansiedad y depresión, en comparación con la población en general (Gurpinar et al, 2019;Henning et al, 2020;Liu et al, 2022;Nasser et al, 2021), en conjunto, estos síntomas psiquiátricos no están asociados a una etapa específica de la enfermedad o a la progresión de Lastre-Meza, Karina Sofía -Barceló Mártínez, Ernesto Alejandro -la misma (Henning et al, 2020). Esto reafirma investigaciones anteriores que indicaron que el paciente con vitiligo es más ansioso, tiende a experimentar mayor sentimiento de desesperanza, baja autoestima, depresión e insatisfacción sexual (Lai, Yew, Kennedy & Schwartz, 2017;Sarhan, Mohammed, Goma & Eyada, 2015).…”
Section: Discusionunclassified